2012
DOI: 10.2172/1048616
|View full text |Cite
|
Sign up to set email alerts
|

Energy Savings Modeling of Standard Commercial Building Re-tuning Measures: Large Office Buildings

Abstract: Today, many large commercial buildings use sophisticated building automation systems (BASs) to manage a wide range of building equipment. While the capabilities of BASs have increased over time, many buildings still do not fully use the BAS's capabilities and the BASs are not properly commissioned, operated or maintained, which leads to inefficient operation, increased energy use, and reduced lifetimes of the equipment. This report investigates the energy savings potential of several common heating, ventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Fernandez et al (2017) showed that applying advanced controls and sensors could result in energy savings of as much as 30% for commercial buildings. Similar conclusions can be drawn for energy savings benefits through utilization of advanced controls in self-tuning for commercial buildings (Fernandez et al 2010(Fernandez et al , 2012(Fernandez et al , 2015.…”
Section: Introductionsupporting
confidence: 69%
“…Fernandez et al (2017) showed that applying advanced controls and sensors could result in energy savings of as much as 30% for commercial buildings. Similar conclusions can be drawn for energy savings benefits through utilization of advanced controls in self-tuning for commercial buildings (Fernandez et al 2010(Fernandez et al , 2012(Fernandez et al , 2015.…”
Section: Introductionsupporting
confidence: 69%
“…Considering a deadband of 6 K, the resulting cooling and heating setpoints cover a wide range of setpoints (16.5 °C to 29.5 °C, respectively). These setpoints are greater than the values used in different studies [18][19][20][21]. For the deadband, we selected 0, 1, 2 K, 3 K (pre-set deadband on the DOE reference buildings), 4 K, 5 K, and 6 K. Again, various values of deadband can be studied based on stakeholders' preferences, however values greater than 6 K would require occupants to pursue individual adaptation procedures to achieve comfort.…”
Section: Methodsmentioning
confidence: 99%
“…The same authors in their previous studies [18] found that extending the setpoint range from 21.1-23.9 °C to 20.6-25 °C reduces between 13 to 28 % HVAC energy consumption on different types of medium-sized office buildings. In another study on the large office DOE reference buildings [20], the authors showed that extending the temperature setpoints range from 21.6 to 22.8 °C to 20.6 to 23.9 °C reduced the energy consumption by 9 to 20% depending on the climate and time of the year. However, the influence of heating and cooling setpoints extension on actual setpoints and deadband remains unclear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A simulation study of energy-saving measures in large office buildings carried out by Pacific Northwest National Labs examined the energy impact of a widened thermostat setpoint range [11]. In a similar fashion, this study used the DOE large office baseline models, which are similar to the medium office building models used in this study.…”
Section: Comparison To Other Simulation Studiesmentioning
confidence: 99%